2023
DOI: 10.1002/ajim.23478
|View full text |Cite
|
Sign up to set email alerts
|

Symptom characteristics of health care workers seeking outpatient psychiatric care during the COVID‐19 pandemic

Abstract: Background: Though there is a growing body of research establishing a broad negative psychological impact of COVID-19 among healthcare workers (HCWs), there are comparably fewer studies evaluating symptom presentation and clinical diagnoses among treatment-seeking HCWs. The present report seeks to fill this gap in the literature by establishing the prevalence of anxiety, depression, post-traumatic stress, alcohol misuse, and well-being among treatment-seeking HCWs.Method: Data were collected from 421 treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…This program included evidence-based resilience workshops, a self-guided mental health app, and individual mental health care in the form of up to 14 sessions of CBT or medication management. Psychiatric symptom severity and DSM-V diagnoses were examined for a first cohort ( N = 427) seeking mental health treatment using some of the same measures reported in the current study 49 . The Doukas et al study reported somewhat higher rates of moderate-to-severe depressive (47%) and anxiety (58%) symptoms based on PHQ-9 and GAD-7 scores relative to the current study, but similar to the current study, the overwhelming majority of patients were diagnosed with depressive, anxiety, or adjustment disorders.…”
Section: Discussionmentioning
confidence: 99%
“…This program included evidence-based resilience workshops, a self-guided mental health app, and individual mental health care in the form of up to 14 sessions of CBT or medication management. Psychiatric symptom severity and DSM-V diagnoses were examined for a first cohort ( N = 427) seeking mental health treatment using some of the same measures reported in the current study 49 . The Doukas et al study reported somewhat higher rates of moderate-to-severe depressive (47%) and anxiety (58%) symptoms based on PHQ-9 and GAD-7 scores relative to the current study, but similar to the current study, the overwhelming majority of patients were diagnosed with depressive, anxiety, or adjustment disorders.…”
Section: Discussionmentioning
confidence: 99%